2020
DOI: 10.1371/journal.pone.0234479
|View full text |Cite
|
Sign up to set email alerts
|

STAT3/SOCS3 axis contributes to the outcome of salmonid whirling disease

Abstract: There are differences in disease susceptibility to whirling disease (WD) among strains of rainbow trout. The North American strain Trout Lodge (TL) is highly susceptible, whereas the German Hofer (HO) strain is more resistant. The suppressor of cytokine signaling (SOCS) proteins are key in inhibiting cytokine signaling. Their role in modulating the immune response against whirling disease is not completely clear. This study aimed at investigating the transcriptional response of SOCS1 and SOCS3 genes to Myxobol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 58 publications
(121 reference statements)
0
18
0
Order By: Relevance
“…Findings of these investigations linked various immune-related genes and pathways with resistance to parasitic infection. Several genes previously linked to parasite resistance including ACAT2 ( 34 ), SOCS3 ( 35 37 ), and IGSF21 ( 38 ) also showed differential expression pattern between tolerant and susceptible birds. These genes are therefore promising candidates for further validation and practical application.…”
Section: Discussionmentioning
confidence: 93%
“…Findings of these investigations linked various immune-related genes and pathways with resistance to parasitic infection. Several genes previously linked to parasite resistance including ACAT2 ( 34 ), SOCS3 ( 35 37 ), and IGSF21 ( 38 ) also showed differential expression pattern between tolerant and susceptible birds. These genes are therefore promising candidates for further validation and practical application.…”
Section: Discussionmentioning
confidence: 93%
“…Our study found that the frequency of Th17 cells in the BA treatment group was significantly reduced, suggesting that BA regulates Treg/Th17 balance and regulates CD4 + T cell differentiation. Suppressor of cytokine signaling family (SOCS1/SOCS3) is necessary for the balance of Treg/Th17 population in different organ diseases ( Qu et al, 2017 ; Wang D. et al, 2018 ; Kmiolek et al, 2020 ; Saleh et al, 2020 ). Therefore, we detected the expression of RORγt, SOCS1, and SOCS3 expression.…”
Section: Resultsmentioning
confidence: 99%
“…Identification of the target gene of microRNA-155 is important for understanding the biological functions of microRNA-155, and is required to investigate a possible mechanism of the regulatory effects of microRNA-155 on VSMC proliferation and migration. According to the target gene prediction data generated by TargetScan ( ), Socs1 was a candidate target based on a study in macrophages ( 28 ). Socs1 is a suppressor of cytokine signalling, which is required for cell growth and survival ( 28 ).…”
Section: Resultsmentioning
confidence: 99%
“…According to the target gene prediction data generated by TargetScan ( ), Socs1 was a candidate target based on a study in macrophages ( 28 ). Socs1 is a suppressor of cytokine signalling, which is required for cell growth and survival ( 28 ). The mRNA levels of Socs1 were significantly increased following transfection with the microRNA-155-mimics, compared with the control ( Fig.…”
Section: Resultsmentioning
confidence: 99%